Urban Pre-service English-as-a-Foreign-Language (EFL) Teachers’ Challenges During Teaching Practicum in Rural Schools: A Photovoice Phenomenological Approach - Mudra, Heri (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
While many previous studies focused on English-as-a-Foreign-Language (EFL) teachers’ teaching practices in urban schools, little study has been indulged regarding pre-service English teachers’ (PSTs) challenges and experiences to practice teaching in a rural school. This study aimed to explore various difficulties encountered by urban PSTs during teaching practicum (TP) in rural schools. A total of seven PSTs enrolled in urban universities were voluntarily involved in a study that involves people’s senses and perceptions, rather than scientific evidence, also known as a phenomenological study. Data were collected through multiple semi-structured interviews, followed by a photovoice approach through which the participants were asked to take emotional photos. The results revealed that the PSTs encountered four main challenges during TP in rural schools, including changes in teacher identity construction, intercultural sensitivity barriers, a lack of supporting resources, and limited teacher professional development. Each challenge was accomplished by photographs representing PSTs’ emotions and feelings, such as a collection of dolls, natural scenery, old-printed books, and blank paper. In conclusion, integrating emotional photos into descriptive exploration is paramount evidence of how the challenges were encountered, managed, and solved for better future teaching and learning practices.